Epidemiology of Serratia Bloodstream Infections Among Hospitalized Children in the United States, 2009–2016. Issue 6 (June 2020) - Johnson, Angelia; Watson, Dave; Dreyfus, Jill; Heaton, Phillip; Lampland, Andrea; Spaulding, Alicen B.
Abstract : Serratia can cause serious bloodstream infections (BSIs). This retrospective cohort study identified 5, 312 pediatric inpatient encounters with BSIs from 2009 to 2016, of which 82 (0.01%) had Serratia BSIs. The rate among hospitalized patients increased significantly from 0.4 in 2009 to 1.0 in 2016 per 10, 000 admissions. Risk factors differed and outcomes were worse for Serratia BSIs compared with non- Serratia BSIs.